2001
DOI: 10.1176/appi.ajp.158.6.952
|View full text |Cite
|
Sign up to set email alerts
|

Morphometry of Individual Cerebellar Lobules in Schizophrenia

Abstract: The authors hypothesize that these morphometric changes may be developmental in origin and possibly related to cortical abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0
5

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(49 citation statements)
references
References 15 publications
2
42
0
5
Order By: Relevance
“…Although no convincing evidence for cerebellar abnormalities were found for adolescent-onset schizophrenia (22), recent post-mortem and neuroimaging studies do indicate cerebellar abnormalities in schizophrenia (23). Again the vermis seems to be involved; several structural neuroimaging studies in schizophrenia have provided evidence for distinct volume reductions involving the vermis, but not the cerebellar hemispheres (24,25). Deleterious effects of antipsychotic medication on brain morphology cannot be ruled out in this research, but a study involving 20 neuroleptic-naïve schizophrenic males also showed reductions of the cerebellar vermis (26).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Although no convincing evidence for cerebellar abnormalities were found for adolescent-onset schizophrenia (22), recent post-mortem and neuroimaging studies do indicate cerebellar abnormalities in schizophrenia (23). Again the vermis seems to be involved; several structural neuroimaging studies in schizophrenia have provided evidence for distinct volume reductions involving the vermis, but not the cerebellar hemispheres (24,25). Deleterious effects of antipsychotic medication on brain morphology cannot be ruled out in this research, but a study involving 20 neuroleptic-naïve schizophrenic males also showed reductions of the cerebellar vermis (26).…”
Section: Introductionmentioning
confidence: 97%
“…In particular, the cerebellar-hypothalamic connection yields an important neuroanatomical pathway (12) Cerebellum activity during positive mood states Wiech et al (11) Positive correlation between cerebellum activity and experience of chronic pain Psychiatry Ichimiya et al (26) Reduced volumes of vermis in neuroleptic naïve schizophrenic patients Loeber et al (24) Reduced volumes of inferior cerebellum in schizophrenia Kyosseva (23) Cerebellar abnormalities in schizophrenic patients Okugawa et al (21) White matter abnormalities in the middle cerebellar peduncles of schizophrenic patients Okugawa et al (25) Smaller volumes of vermis in chronic schizophrenia Soares & Mann (27) Depression linked to reduced volumes of the cerebellum Beyer et al (29) Volume reductions of vermis associated with depression Leroi et al (28) Degenerative cerebellar diseases associated with depression Neil et al (30) Vermal volume reductions in manic-depressive disorder CCAS: Cerebellar Cognitive Affective Syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…A post mortem-study of schizophrenia demonstrated an up-regulation of cerebellar extracellular signal-regulated kinase (ERK), a protein involved in synaptic development, dendritic growth, and cell death (Kyosseva, 2003). Schizophrenia also has been associated with smaller whole cerebellum (Keller et al, 2003) and vermal volume Ichimiya et al, 2001;Loeber et al, 2001). Interestingly, cerebellar volume may be associated with poor long-term outcome (Wassink et al, 1999) and cognitive dysfunction (Levitt et al, 1999;Wassink et al, 1999;Ho et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…However, findings from studies of gross cerebellum volume have not gone unchallenged and often vary both within and between studies (e.g., Ichimiya et al, 2001;Szesko et al, 2003a;Szesko et al, 2003b;Keller et al 2003;James et al, 2004;Shin et al, 2005). Since information processing functions of the cerebellum may be characterized by each subregion's distinct connectivity (O'Hearn and Molliver, 2001), the greatest weakness of these volumetric investigations is that subregions of the cerebellum, specifically, the anterior and posterior lobules, have not been adequately studied (see Loeber et al, 2001, for an exception).…”
Section: Introductionmentioning
confidence: 99%
“…A disturbance of morphological and functional lateralization of the cerebellum is reportedly involved in human neurodevelopmental disorders with cognitive impairments, such as autism [45], schizophrenia [46,47], dyslexia [48], and attention deficit hyperactivity disorder [49]. The direction and extent of the cerebellar torque asymmetry varied depending on species [13,14,34], the hand preference [13], and/or sex [34], independent of genetic factors [13].…”
Section: Discussionmentioning
confidence: 99%